Ceria Nanoparticles Meet Hepatic Ischemia‐Reperfusion Injury: The Perfect Imperfection. Issue 40 (16th August 2019) - Ni, Dalong; Wei, Hao; Chen, Weiyu; Bao, Qunqun; Rosenkrans, Zachary T.; Barnhart, Todd E.; Ferreira, Carolina A.; Wang, Yanpu; Yao, Heliang; Sun, Tuanwei; Jiang, Dawei; Li, Shiyong; et al.
Abstract: The mononuclear phagocyte system (MPS, e.g., liver, spleen) is often treated as a "blackbox" by nanoresearchers in translating nanomedicines. Often, most of the injected nanomaterials are sequestered by the MPS, preventing their delivery to the desired disease areas. Here, this imperfection is exploited by applying nano‐antioxidants with preferential liver uptake to directly prevent hepatic ischemia‐reperfusion injury (IRI), which is a reactive oxygen species (ROS)‐related disease. Ceria nanoparticles (NPs) are selected as a representative nano‐antioxidant and the detailed mechanism of preventing IRI is investigated. It is found that ceria NPs effectively alleviate the clinical symptoms of hepatic IRI by scavenging ROS, inhibiting activation of Kupffer cells and monocyte/macrophage cells. The released pro‐inflammatory cytokines are then significantly reduced and the recruitment and infiltration of neutrophils are minimized, which suppress subsequent inflammatory reaction involved in the liver. The protective effect of nano‐antioxidants against hepatic IRI in living animals and the revealed mechanism herein suggests their future use for the treatment of hepatic IRI in the clinic. Abstract : Although the importance of inhibiting oxidative stress has been recognized for several decades, hepatic ischemia‐reperfusion injury (IRI) remains challenging to treat. Ceria nanoparticles are found to efficiently alleviate the clinical symptoms of hepatic IRI by scavenging reactive oxygen species, inhibiting the activation of Kupffer cells and monocyte/macrophage cells. The released pro‐inflammatory cytokines are significantly reduced and the recruitment and infiltration of neutrophils are then inhibited.